TYPES OF NEUROSES IN CHILDREN AND THEIR PREVENTION. - Ozodova Diana Sardor kizi; Saidkhodjaeva S.N; Nurkhodjaev S.N. (Scholar Express Journals, 2024)
This article aims to explore the various types of neuroses commonly observed in children, including anxiety disorders, obsessive-compulsive disorder (OCD), and phobias, among others. It delves into the literature surrounding the causes and risk factors contributing to the development of neuroses in childhood. Additionally, the article discusses preventive measures and intervention strategies that can help mitigate the onset and severity of neuroses in children, thereby promoting their mental well-being and overall quality of life
Keywords: Neuroses; children; anxiety disorders; ocd